Reduction mammaplasty improves levels of anxiety, depression and body image satisfaction in patients with symptomatic macromastia in the short and long term - Esther Pérez-Panzano; Ana Gascón-Catalán; Ramón Sousa-Domínguez; Patricia Carrera-Lasfuentes; Javier García-Campayo; Antonio Güemes-Sánchez (Journal of Psychosomatic Obstetrics and Gynecology, 2017)
Objective: To evaluate the psychological consequences (anxiety, depression and body image dissatisfaction) of symptomatic macromastia and the effectiveness of breast reduction surgery in re-establishing the mental health of the patient in the short and long term. Method: 119 patients over 18 years old who had been diagnosed with symptomatic macromastia were assessed, before surgery, one month after the operation and one year later. Patients completed the Hospital Anxiety and Depression Scale (HADS) and the Body Image Dissatisfaction subscale of the Eating Disorders Inventory (EDI-2). Participants were also asked about their physical appearance, social relationships and their satisfaction with regards to clothing and dress. Results: The average age of the patients was 40.7 (SD = 12.02), 80.2% had a body mass index ≥25 kg/m2. Before surgery, we found psychological distress with values indicating clinical anxiety and body image dissatisfaction. Younger women (< 36 years old) were more psychologically affected. At one month after surgery, there were significant improvements: there were lower scores for anxiety (p < 0.001), depression (p < 0.001) and body image dissatisfaction (p < 0.001). When compared with the pre-surgery scores, all these results showed improvement one year after the intervention (p < 0.001). There were also improvements in social relationships (p < 0.001) and satisfaction with clothing and dress. Conclusion: Reduction mammaplasty can alleviate the psychological impact of symptomatic macromastia.